2021
DOI: 10.1177/0885066621993739
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban Anticoagulation for Adult Extracorporeal Membrane Oxygenation: A Systematic Review

Abstract: Background: Heparin is the widely used anti-coagulation strategy for patients on extracorporeal membrane oxygenation (ECMO). Nevertheless, heparin-induced thrombocytopenia (HIT) and acquired anti-thrombin (AT) deficiency preclude the use of heparin requiring utilization of an alternative anticoagulant agent. Direct thrombin inhibitors are being proposed as potential alternatives with argatroban as one of the main agents. We aimed to review the evidence with regard to safety and efficacy of argatroban as a pote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 64 publications
(262 reference statements)
1
52
2
Order By: Relevance
“…It concluded that argatroban appeared to be a feasible, effective and safe anticoagulant for critically ill ARDS patients undergoing extracorporeal lung support. A systematic review has similar findings [29] in adult patients on ECMO. A retrospective observational study [30] also indicated that argatroban was safe and useful in patients who were suspected of having HIT and were started on argatroban, but were ultimately found to have non-HIT.…”
Section: Discussionsupporting
confidence: 53%
“…It concluded that argatroban appeared to be a feasible, effective and safe anticoagulant for critically ill ARDS patients undergoing extracorporeal lung support. A systematic review has similar findings [29] in adult patients on ECMO. A retrospective observational study [30] also indicated that argatroban was safe and useful in patients who were suspected of having HIT and were started on argatroban, but were ultimately found to have non-HIT.…”
Section: Discussionsupporting
confidence: 53%
“…75 A recent systematic review included four cohort studies and 9 case series totaling 307 patients with the use of argatroban during ECMO. 76 A continuous infusion without a loading dose was used in the majority of cases, although infusion rates varied widely. aPTT was most often used for monitoring but without consensus targets.…”
Section: Argatrobanmentioning
confidence: 99%
“…Bleeding and thromboembolic complication rates were found to be comparable to those of patients who received UFH. 76 For argatroban, the SCA has issued a Class IIb recommendation for patients with renal failure and HIT who require CPB, with warning of increased bleeding risk. 11 Currently, the Extracorporeal Life Support Organization (ELSO) guidelines recommend consideration of the aforementioned three parenteral DTIs as alternative anticoagulants for patients with HIT.…”
Section: Argatrobanmentioning
confidence: 99%
“…This has led to additional pressures on ECMO centres and highlighted the potential role of ECMO in the treatment of COVID-19. 3,4 The purpose of this report is to provide insights from the qualitative literature on the perspectives of those engaging with ECMO, including patients, their family, and their caregivers to support decision-making around the provision and delivery of ECMO for respiratory failure.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…I question, what are we actually doing? Are we actually treating this person like a human being or is (the patient) becoming a lab experiment (p. [3][4]." 11 In this same study (evaluating the ethics consultation protocol), particular cases were evoked by clinicians during interviews.…”
Section: Ecmo As Escalating Interventionmentioning
confidence: 99%